Acompanhamento farmacoterapêutico de gestantes em tratamento para toxoplasmose: descrição e avaliação do serviço com indicadores - Sampaio, Renata Sousa (2024)
Toxoplasmosis, caused by the parasite Toxoplasma gondii and with variable prevalence between countries, is considered a public health problem, as infection in pregnant women can cause serious damage to the fetus. The Brazilian Ministry of Health recommends monitoring and monitoring cases, in addition to reporting the condition to surveillance bodies at different levels of care. The Pharmacotherapeutic Follow-up of pregnant women in Primary Care aims to monitor the patient in order to guarantee access, adherence to treatment, notification of cases and identification of problems related to medicines. The present work aimed to study Pharmacotherapeutic Follow-up provided to pregnant women undergoing treatment for toxoplasmosis in the Primary Health Care Units (PHCU) in Fortaleza, Ceará, between august 2022 and july 2023. This is an observational, cross-sectional study with a retrospective and quantitative approach carried out in three stages: Stage 1 = Description of the clinical service of Pharmacotherapeutic Monitoring in Primary Health Care in Fortaleza/Ceará; Stage 2 = Design of the pharmacoepidemiological and sociodemographic profile; Stage 3 = Description and evaluation of Pharmacotherapeutic Follow-up of patients with gestational toxoplasmosis with indicators of structure, process and result. During the research period, 149 pregnant women were given medication for toxoplasmosis, of which 41 continued to be monitored by the pharmacist. Of these, 68.3% were over 25 years old, 48.8% had completed high school and 68.3% did not report other comorbidities. Pharmacotherapeutic Follow-up is carried out in 12.4% of the PHCU. Of these, 64.3% have an office exclusively for pharmaceutical consultations. Regarding monitoring, 75.6% started consultations and use of medications in the 2nd trimester of pregnancy, with an average number of 3.7 ± 1.4 consultations per patient. The majority (97.6%) of consultations were carried out in person. Pharmacists carried out 56.1% of notifications of gestational toxoplasmosis in the study population.The serological profile with reactive IgM and IgG was predominant (90.2%). Regarding medication use, 58.5% used five or more medications throughout the follow-up and 58.5% had a medication- related problem (DRP), of which 47.5% were related to administration and/or adherence to treatment and DRP 5 was the most frequent (45%). Spiramycin was the most prescribed medication (78.5%) and the one most associated with the appearance of adverse drug reactions (ADR) (71.4%). However, the majority (65.9%) of patients did not report ADR. Among the pharmaceutical interventions (PI) carried out (158), 91.8% were related to patient education actions. Most PI were appropriate (98.7%) and significant (92.9%). Regarding outcomes, 75.6% completed follow-up and 19.5% reported problems with treatment adherence. The total acceptance rate of FI was 79.7% and 46.1% among health professionals. The study made it possible to understand the profile of the patients being monitored, the strengths and main weaknesses of the Pharmacotherapeutic Monitoring service, generating data for developing strategies for improvement and correction of flaws, contributing to the strengthening of pharmaceutical care actions in primary care.